A Scoping Review of Empirical Research Relating to Quality and Effectiveness of Research Ethics Review. - Stuart G Nicholls; Tavis P Hayes; Jamie C Brehaut; Michael McDonald; Charles Weijer; Raphael Saginur; Dean Fergusson (PLoS ONE)
Background To date there is no established consensus of assessment criteria for evaluating research ethics review. Methods We conducted a scoping review of empirical research assessing ethics review processes in order to identify common elements assessed, research foci, and research gaps to aid in the development of assessment criteria. Electronic searches of Ovid Medline, PsychInfo, and the Cochrane DSR, ACP Journal Club, DARE, CCTR, CMR, HTA, and NHSEED, were conducted. After de-duplication, 4234 titles and abstracts were reviewed. Altogether 4036 articles were excluded following screening of titles, abstracts and full text. A total of 198 articles included for final data extraction. Results Few studies originated from outside North America and Europe. No study reported using an underlying theory or framework of quality/effectiveness to guide study design or analyses. We did not identify any studies that had involved a controlled trial--randomised or otherwise--of ethics review procedures or processes. Studies varied substantially with respect to outcomes assessed, although tended to focus on structure and timeliness of ethics review. Discussion Our findings indicate a lack of consensus on appropriate assessment criteria, exemplified by the varied study outcomes identified, but also a fragmented body of research. To date research has been largely quantitative, with little attention given to stakeholder experiences, and is largely cross sectional. A lack of longitudinal research to date precludes analyses of change or assessment of quality improvement in ethics review.